The Impact of Fructose on Renal Function and Blood Pressure - Marek Kretowicz; Richard J. Johnson; Takuji Ishimoto; Takahiko Nakagawa; Jacek Manitius (International Journal of Nephrology)
Fructose is a sugar present in sucrose, high-fructose corn syrup, honey, and fruits. Fructose intake has increased markedly in the last two centuries, primarily due to increased intake of added sugars. Increasing evidence suggests that the excessive intake of fructose may induce fatty liver, insulin resistance, dyslipidemia, hypertension, and kidney disease. These studies suggest that excessive intake of fructose might have an etiologic role in the epidemic of obesity, diabetes, and cardiorenal disease.